2013
DOI: 10.4049/jimmunol.1301175
|View full text |Cite
|
Sign up to set email alerts
|

The Road to Memory: An Early Rest for the Long Journey

Abstract: Central memory T lymphocytes were reported to develop after acute but not chronic infection, which prompted this feasibility study on generating long-term CD8 T cells ex vivo, by applying a culture condition that simulates an acute infection. During 35 d of culture, naive T cells (CD45RA+, CD127+, CCR7+, CD62L+, CXCR3+) first developed into effector T cells (CD45RA+/−, CD127+/−, CCR7+/−, CD62L+, CXCR3+), followed by three intermediate stages: intermediate T cells 1 (CD45RO+, CD127+/−, CCR7+, CD62L+, CXCR3+), i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 48 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…Complex immunophenotyping of the leukocyte composition in the blood can be helpful in the diagnosis and therapy of diseases such as leukemia , lymphomas , autoimmune and infectious diseases and immunodeficiencies such as AIDS . For this purpose, leukocytes labeled with fluorochrome‐conjugated antibodies are identified and quantified using up to 10‐color flow cytometry (FCM).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Complex immunophenotyping of the leukocyte composition in the blood can be helpful in the diagnosis and therapy of diseases such as leukemia , lymphomas , autoimmune and infectious diseases and immunodeficiencies such as AIDS . For this purpose, leukocytes labeled with fluorochrome‐conjugated antibodies are identified and quantified using up to 10‐color flow cytometry (FCM).…”
mentioning
confidence: 99%
“…In 2011, the Leipzig Research Centre for Civilization Diseases (LIFE) started a prospective population‐based epidemiological study in Leipzig. Within the LIFE study, subjects undergo a comprehensive program including blood sampling, medical examinations, interviews, and questionnaires with the aim to identify risk factors associated with frequent civilization diseases such as diabetes, obesity, and cardiovascular diseases; to find new molecular and cellular biomarkers for early disease diagnosis and to provide new methods for the treatment of these lifestyle diseases.…”
mentioning
confidence: 99%
“…To study the potential role of CD3 + γδTCR + cells after infection, the phenotype of γδT cells was examined. CD127, CD34 and CD62L are T cell activation-associated molecules [21][22][23]. CD34 serves as a ligand for CD62L, CD34 and CD62L primarily regulate the proliferation and migration of leukocytes to in ammatory sites and lymph nodes [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Expressing CD62L and CCR7, Naïve T and central memory T cells can home to SLOs. Activated by APCs, effector memory T and effector T cells lose the expression of CD62L and CCR7, emigrate from SLOs into the peripheral inflammatory tissues [46] [48] . Our results showed that MSCs/CCR7 infusion dramatically made T cells in SLOs less proliferous and cytotoxic.…”
Section: Discussionmentioning
confidence: 99%